2013
DOI: 10.1002/jnr.23314
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Wnt3a facilitates the proliferation and neural differentiation of neural stem cells in vitro and after transplantation into an injured rat retina

Abstract: Neural stem cell-based therapy is a promising option for repair after injury. However, poor stem cell proliferation and insufficient differentiation of the stem cells into neurons are still difficult problems. The present study investigated whether transplantation of neural stem cells (NSCs) genetically modified to express Wnt3a is a promising approach to overcome these difficulties. We explored the possibility that Wnt3a might contribute to the therapeutic effect of NSC transplantation in retinal repair. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…The isolation, culture, and identification of NSCs were done according to our earlier published studies (Yang et al, 2014). Briefly, pregnant Sprague–Dawley rats (Shanghai Experimental Animal Center, Shanghai, China) were deeply anesthetized with a mixture of ketamine and xylazine (3:1 ratio) and carefully dissected to get embryos (embryonic day 14).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The isolation, culture, and identification of NSCs were done according to our earlier published studies (Yang et al, 2014). Briefly, pregnant Sprague–Dawley rats (Shanghai Experimental Animal Center, Shanghai, China) were deeply anesthetized with a mixture of ketamine and xylazine (3:1 ratio) and carefully dissected to get embryos (embryonic day 14).…”
Section: Methodsmentioning
confidence: 99%
“…NSCs were engrafted into the subretinal space immediately after the optic nerve crush with a transscleral approach as previous procedure (Yang et al, 2014). Briefly, under ophthalmic microscopic observation, the temporal conjunctiva was dissected at the limbus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Meanwhile, HUMSCs have been ultimately converted into induced pluripotent stem cells via the codelivery of Yamanaka factors (c-Myc, Klf4, Sox2, and Oct4) using calcium phosphate nanoparticles, 43 which illustrated the remarkable inducibility of HUMSCs based on a nonviral gene-delivery system. In addition, the overexpression of Wnt3a 44 can direct the differentiation of neural stem cells into neurons both in vitro and in vivo by activating Wnt signaling, which is also a requirement for the maintenance, proliferation, and survival of neural progenitors when cultured under neurosphere conditions. 45 Previous studies have demonstrated that the overexpression of Wnt3a in highly self-renewable cells 46,47 might contribute to the formation and proliferation of neural cells, which could be a new and safe method for the recovery of spinal cord injury.…”
mentioning
confidence: 99%